Hormonal mechanisms of cooperative behaviour - Soares, Marta C. (2012)
Research on the diversity, evolution and stability of cooperative behaviour has generated a considerable body of work. As concepts simplify the real world, theoretical solutions are typically also simple. Real behaviour, in contrast, is often much more diverse. Such diversity, which is increasingly acknowledged to help in stabilizing cooperative outcomes, warrants detailed research about the proximate mechanisms underlying decision-making. Our aim here is to focus on the potential role of neuroendocrine mechanisms on the regulation of the expression of cooperative behaviour in vertebrates. We first provide a brief introduction into the neuroendocrine basis of social behaviour. We then evaluate how hormones may influence known cognitive modules that are involved in decision-making processes that may lead to cooperative behaviour. Based on this evaluation, we will discuss specific examples of how hormones may contribute to the variability of cooperative behaviour at three different levels: (i) within an individual; (ii) between individuals and (iii) between species. We hope that these ideas spur increased research on the behavioural endocrinology of cooperation.